PENGARUH Pengaruh Media Sepatu Pintar Terhadap Motorik Halus Pada Anak Kelompok B Di TK ABA Weru - Indy Rahmawati (Universitas Muhammadiyah Gresik, 2021)
This research is motivated by the lack of fine motor skills in terms of being skilled at using the hands of group B children. In this case the researcher saw that the child was less thorough, less skilled and quickly bored in doing the task so that the task was not completed as expected by the teacher. Seeing this, the researchers created a special media, namely smart shoes learning media. Smart shoe learning media is a media created to train children's fine motor development skills, smart shoe media is designed to be attractive so that when learning children are not easily bored doing activities. The formulation of the problem in this study is whether there is an effect of smart shoes media on fine motor skills in group B children at ABA Weru Kindergarten. This study uses a quantitative method of Pre-Experimental Design (Pre-Experiment Design). The design used in this study is the One Group Pre-Post Test Design. In this study the sampling used Nonprobability Sampling with Purposive Sampling technique, the sample used was 30 children. The data obtained in the study showed that the average pretest and posttest score, which was 162, increased to 205 when treatment was given using smart shoes. The results of the statistical test output analysis in this study are Tcount > Ttable, namely 4,744 > 2,042. So it can be concluded that Ha is accepted to support the hypotests formulated earlier, with the acceptance of the hypothesis which shows that there is an influence of smart shoes media on fine motor skills in group B children in ABA Weru Kindergarten. Keywords: Media Smart Shoes, Fine Motoric, Group B Children